Sockupied : 20 knit projects to satisfy your sock obsession - Merrow, Anne, 1977- (Interweave, a division of F+W Media, 2014)
Slightly obsessed with sock knitting? Get Sockupied! Sockupied is a groundbreaking eMag that began in 2010. Now available for the first time in book form, Sockupied brings knitters a collection of 20 sock patterns specially chosen from its first 10 issues. Simple patterns appeal to beginners, while stunning colorwork and unusual construction will tempt seasoned sock knitters. The book features 6 toe-up patterns as well as those with standard top-down construction, and projects include basic socks for beginners as well as cables, lace, colorwork, and textured patterns. An all-star roster of sock designers contribute patterns: Cookie A, Star Athena, Ann Budd, Cat Bordhi, Deborah Newton, and many more. In addition, a variety of technical articles will round out the book: info on various cast-ons and bind-offs, darning, and converting patterns form top-down to toe-up and vice versa. Knitters who are slightly obsessed with knitting socks will want to get their hands on Sockupied!